2017
DOI: 10.1371/journal.pone.0170552
|View full text |Cite|
|
Sign up to set email alerts
|

RNA and DNA Targeting by a Reconstituted Thermus thermophilus Type III-A CRISPR-Cas System

Abstract: CRISPR-Cas (clustered regularly interspaced short palindromic repeats-CRISPR-associated) systems are RNA-guided adaptive immunity pathways used by bacteria and archaea to defend against phages and plasmids. Type III-A systems use a multisubunit interference complex called Csm, containing Cas proteins and a CRISPR RNA (crRNA) to target cognate nucleic acids. The Csm complex is intriguing in that it mediates RNA-guided targeting of both RNA and transcriptionally active DNA, but the mechanism is not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 47 publications
5
118
0
Order By: Relevance
“…2c, only CTR activated the LdCsm DNase, indicating that mismatches between the 3ʹ anti-tag of the target RNA and the corresponding 5ʹ tag of crRNA are essential for the activation. These results are in good agreement with those reported for other characterized type III CRISPR-Cas systems 15,17,19,20,31,34,35 . We further tested the minimal concentration of CTR is required for the ssDNase activity of LdCsm.…”
Section: Delbrueckii Subsp Bulgaricus Encodes a Novel Iii-a Crispsupporting
confidence: 92%
See 2 more Smart Citations
“…2c, only CTR activated the LdCsm DNase, indicating that mismatches between the 3ʹ anti-tag of the target RNA and the corresponding 5ʹ tag of crRNA are essential for the activation. These results are in good agreement with those reported for other characterized type III CRISPR-Cas systems 15,17,19,20,31,34,35 . We further tested the minimal concentration of CTR is required for the ssDNase activity of LdCsm.…”
Section: Delbrueckii Subsp Bulgaricus Encodes a Novel Iii-a Crispsupporting
confidence: 92%
“…Biochemical and structural analyses of different type III CRISPR-Cas systems have revealed that the HD domain is responsible for ssDNA cleavage 15,19,20,31,34,35 , Palm1 and Palm2 domains function in cOA synthesis [38][39][40][41]43 whereas the Linker domain plays a regulatory role in both target RNA-activated DNA cleavage and cOA synthesis 54 . However, it remains unclear whether a concerted action of different Cas10 domains would be required to yield Csm DNase with optimal activity.…”
Section: Multiple Cas10 Domains Contribute To the Ldcsm Dnase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in several other systems, hybridization with the protospacer sequence alone is not sufficient for DNase activation. In these systems, the DNase remains inactive unless a non-complementary sequence extends from the protospacer into the 5′-repeat [72,73,75], and in some systems (e.g. Type III-B Cmr system in P. furiosus ) this 3′ non-complementary RNA sequence must meet specific sequence requirements [70].…”
Section: Regulation Of Class 1 Nucleases That Are Essential For Intermentioning
confidence: 99%
“…Thus far, ring nucleases have only been identified in the crenarchaea, and, as highlighted by Mo and Marraffini [14], the enzyme(s) responsible for cOA degradation in bacteria remain unknown. The type III CRISPR system of the bacterium Thermus thermophilus HB8 has been investigated [15,16], and its CRISPR ancillary ribonuclease TTHB152 was among the first shown to be activated by cA4 [10]. The type III CRISPR locus of T. thermophilus also encodes an uncharacterised CARF domain-containing protein, TTHB144, which was reported to be Csm6-like [17].…”
Section: Introductionmentioning
confidence: 99%